EFFECTIVE STRATEGY TO MINIMIZE ASPHALTENE PRECIPITATION DURING C02 INJECTION - BURIRO, MUHAMMAD ALI (2013)
Unstable Asphaltene is major concern in oil reservoir under C02 Gas injection due to its unfavorable damage to reservoir which cannot be recovered. It can plug the pore spaces or can cause wettability alterations inreservoir. It can also plug wells and flow lines through deposition and also cause separation difficulties at the separation facilities. Taking preventive measures is always awise solution rather than attempting to resolve issues as they occur. This study proposes a strategy to predict and prevent Asphaltene Precipitation. Dealing with unstable Asphaltene in light crude oil was divided into three main parts that were evaluating Asphaltene colloidal stability * 3-5— Asphaltene Prediction and Asphaltene prevention. Saturates, aromatics, resins and asphaltene (SARA) analysis was conducted to measure the colloidal stability.